2020
DOI: 10.1111/bcp.14428
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐drug interaction between warfarin and statins: A Danish cohort study

Abstract: Initiation of statin treatment is suggested to increase the international normalised ratio (INR) among warfarin users. However, available data is limited and conflicting. We conducted a register‐based cohort study to evaluate the drug‐drug interaction between warfarin and statins. By linking data on INR measurements and filled prescriptions, we identified warfarin users 2000‐2015 initiating simvastatin (n = 1363), atorvastatin (n = 165) or rosuvastatin (n = 23). Simvastatin initiation led to an increase in mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Warfarin is a routinely administered anticoagulant for thromboembolic therapy; nevertheless, due to its narrow therapeutic index, individual dosage responses, and drug interactions, it is sensitive to dose change [ 15 , 16 ]. Statins and warfarin have similar metabolic patterns, with both being metabolized by cytochrome P450 (CYP) enzymes in the liver, mainly CYP2C9 and CYP3A4 [ 15 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Warfarin is a routinely administered anticoagulant for thromboembolic therapy; nevertheless, due to its narrow therapeutic index, individual dosage responses, and drug interactions, it is sensitive to dose change [ 15 , 16 ]. Statins and warfarin have similar metabolic patterns, with both being metabolized by cytochrome P450 (CYP) enzymes in the liver, mainly CYP2C9 and CYP3A4 [ 15 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that the concomitant use of statin and warfarin could lead to an interaction that may put patients at increased risk of bleeding-notably through elevation of the international normalized ratio. [28][29][30][31] Evidence from individual studies on humans indicated that the use of oral anticoagulants such as warfarin could increase the risk of GIB, especially in the presence of other risk factors such as the use of drugs that increase risk of bleeding. 8,32,33 Previously published preclinical works based on animal studies reported on the association between the use of statins and GIB.…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51][52][53][54] An analysis of a large national database registry demonstrated that atorvastatin, rosuvastatin, and simvastatin all increased the mean INR by ≈ 0.3, with a peak at around 4 weeks. 55 This degree of INR elevation was not thought to be clinically significant to warrant a preemptive dose reduction of warfarin. The authors of this study recommended close monitoring after initiation of these statins, as patients with certain CYP450 genotypes may be more vulnerable.…”
Section: Cardiovascular Medicationsmentioning
confidence: 99%
“…The authors of this study recommended close monitoring after initiation of these statins, as patients with certain CYP450 genotypes may be more vulnerable. 49,55 The mechanism of this interaction for atorvastatin, rosuvastatin, and simvastatin is likely a combination of displacement of warfarin from plasma protein binding in addition to inhibition of CYP3A4, which will increase the unbound plasma concentration of warfarin. 51,54 Fluvastatin, on the other hand, inhibits CYP450 2C9, and likely potentiates warfarin to a greater extent given its effect on the more potent S-isomer of warfarin.…”
Section: Cardiovascular Medicationsmentioning
confidence: 99%